Effect of arbuscular mycorrhizal symbiosis on growth and biochemical characteristics of Chinese fir (Cunninghamia lanceolata) seedlings under low phosphorus environment - Tian, Yunlong; Xu, Jingjing; Li, Linxin; Farooq, Taimoor Hassan; Ma, Xiangqing; Wu, Pengfei (PeerJ, 2024)
Background The continuous establishment of Chinese fir (Cunninghamia lanceolata) plantations across multiple generations has led to the limited impact of soil phosphorus (P) on tree growth. This challenge poses a significant obstacle in maintaining the sustainable management of Chinese fir. Methods To investigate the effects of Arbuscular mycorrhizal fungi (AMF) on the growth and physiological characteristics of Chinese fir under different P supply treatments. We conducted an indoor pot simulation experiment in the greenhouse of the Forestry College of Fujian Agriculture and Forestry University with one-and-half-year-old seedlings of Chinese fir from March 2019 to June 2019, with the two P level treatment groups included a normal P supply treatment (1.0 mmol L−1 KH2PO4, P1) and a no P supply treatment (0 mmol L−1 KH2PO4, P0). P0 and P1 were inoculated with Funneliformis mosseae (F.m) or Rhizophagus intraradices (R.i) or not inoculated with AMF treatment. The AMF colonization rate in the root system, seedling height (SH), root collar diameter (RCD) growth, chlorophyll (Chl) photosynthetic characteristics, enzyme activities, and endogenous hormone contents of Chinese fir were estimated. Results The results showed that the colonization rate of F.m in the roots of Chinese fir seedlings was the highest at P0, up to 85.14%, which was 1.66 times that of P1. Under P0 and P1 treatment, root inoculation with either F.m or R.i promoted SH growth, the SH of R.i treatment was 1.38 times and 1.05 times that of F.m treatment, respectively. In the P1 treatment, root inoculation with either F.m or R.i inhibited RCD growth. R.i inhibited RCD growth more aggressively than F.m. In the P0 treatment, root inoculation with F.m and R.i reduced the inhibitory effect of phosphorus deficiency on RCD. At this time, there was no significant difference in RCD between F.m, R.i and CK treatments (p < 0.05). AMF inoculation increased Fm, Fv, Fv/Fm, and Fv/Fo during the chlorophyll fluorescence response in the tested Chinese fir seedlings. Under the two phosphorus supply levels, the trend of Fv and Fm of Chinese fir seedlings in different treatment groups was F.m > R.i > CK. Under P0 treatment, The values of Fv were 235.86, 221.86 and 147.71, respectively. The values of Fm were 287.57, 275.71 and 201.57, respectively. It increased the antioxidant enzyme activity and reduced the leaf’s malondialdehyde (MDA) content to a certain extent. Conclusion It is concluded that AMF can enhance the photosynthetic capacity of the host, regulate the distribution of endogenous hormones in plants, and promote plant growth by increasing the activity of antioxidant enzymes. When the P supply is insufficient, AMF is more helpful to plants, and R.i is more effective than F.m in alleviating P starvation stress in Chinese fir.
Keywords: Arbuscular mycorrhizal fungi; Chlorophyll fluorescence; Antioxidant enzyme; Photosynthetic capacity; Endogenous hormones; Nutrient stress; Chinese fir